Mid-term result of atrioventricular valve replacement in patients with a single ventricle. (2nd June 2018) - Sughimoto, Koichi; Hirata, Yasutaka; Hirahara, Norimichi; Miyata, Hiroaki; Suzuki, Takaaki; Murakami, Arata; Miyaji, Kagami; Takamoto, Shinichi
Abstract: OBJECTIVES: Atrioventricular valve replacement is the last option to treat the atrioventricular valve regurgitation in single ventricle. This study investigates the mid-term outcomes of the atrioventricular valve replacement based on the Japan Cardiovascular Surgery Database registry. METHODS: From 2008 to 2014, 56 patients [34 males (61%) and 22 females (39%)] with a single ventricular circulation, underwent atrioventricular valve replacement. Questionnaires were collected to review operative data, mid-term mortality, morbidity and redo replacement. Risk factor analysis was performed by the Cox regression model for death and redo replacement. RESULTS: Heterotaxy, a right systemic ventricle and a common atrioventricular valve was present in 46% (26/56), 64% and 57% of patients, respectively. The most common timings for atrioventricular valve replacement were the interstage between the second and third palliations (34%) and after the Fontan operation (34%). Twenty died during the 3.7 ± 2.6-year follow-up. Eleven received redo atrioventricular replacement. The cumulative incidences of redo atrioventricular valve replacement and survival at 3 years were 20% [95% confidence interval (CI) 9–30] and 66% (95% CI 55–80), respectively. Univariable Cox regression analysis revealed that a tricuspid valve was a risk factor for redo valve replacement [hazard ratio (HR) 6.76, 95% CI 1.79–25.6; P  = 0.005] and that young age was a risk factor for death (HR 0.77, 95% CI 0.62–0.96; P  = 0.019). Fourteen patients required a pacemaker implantation. CONCLUSIONS: Valve replacement for uncontrollable atrioventricular valve regurgitation in single ventricular circulation was associated with a moderately high risk of death, redo replacement and pacemaker implantation, whereas valve replacement at a later period and with a larger prosthetic valve size was associated with low mortality.